Use of the high density bovine microarray for the generation of an alpaca Vicugna pacos single nucleotide polymorphism physical map - Mamani C. (2020)
The aim of this study was to develop a preliminary physical map of single nucleotide polymorphisms (SNPs) in alpaca using an alpaca/hamster radiation hybrid panel and a bovine high- density SNP genotyping microarray (BovineHD BeadChip-Illumina). The methodology included genotyping 92 alpaca/hamster hybrid cell clones, and four control samples (male alpaca, female alpaca, hamster and 1:10 DNAmixture) with the microarray. After genotyping the alpaca and hamster DNA control samples, only bovine SNPs with a call frequency of 1 were retained. The SNPs identified in the alpaca DNA samples were then filtered to remove those also found in the hamster. From the remaining alpaca SNPs, to decrease the probability of false positives, only those with a call frequency from 0.2 to 0.8 in the 92 hybrid clone samples were retained for the final analysis. The remaining alpaca specific SNPs were tabulated in MapMaker format and were analysed with the Carthagene software to identify linkage groups. The linkage groups were mapped to the reference genome Vicugna_pacos-2.0.2, using the BLAST software and the SHORTBLAST command on the Galaxy platform. The two alpaca control samples had 294 165 SNPs with positive signals in the bovine microarray. After eliminating the most common hamster SNPs and the most-likely false positives, 2924 SNPs remained. These were assigned to 33 linkage groups encompassing 216 SNPs. The estimated distance between these SNPs ranged from 65.3 and 671.9 cR, with a logarithm of the odds (LOD) >6.0. Finally, a total of 31 SNPs was found in the reference genome (E-value <0.05). © 2020 Universidad Nacional Mayor de San Marcos. All rights reserved.